Isolasi Fungi Tanah Muara Desa Pasir Putih Kabupaten Situbondo serta Penapisan Aktivitas Antibakteri terhadap Staphylococcus aureus - Ziyan Nihlatul Millah; Bawon Triatmoko; Ari Satia Nugraha (JURNAL ILMU KEFARMASIAN INDONESIA, 2022)
Healthcare-Associated Infections (HAIs) is a bacterial infections in Indonesia caused by Staphylococcus aureus. According to the World Health Organization (WHO), the prevalence of HAIs in developing countries varies between 5.7% and 19.1% with a combined prevalence of 10.1%. The prevalence of HAIs in Indonesia is 7.1%. Infections caused by bacteria are a life-threatening disease, which needs to be treated immediately by administering antibacterial agents. One of the natural products with potential as new antibacterial agents, such as soil fungi. This research aims to discover the Antibacterial activity of fungi on estuary land at Pasir Putih village, Situbondo, East Java. This research was initiated by growing the soil on the PDA media to isolate six fungi which were labeled as IS-B1-A1, IS-B1-A2, IS-B1-T1, IS-B1-T2, IS-B1-B1, and IS-B1-B2. All the isolated fungi were separately fermented for 14 d and extracted using ethyl acetate before the microdilution test. The result of antibacterial testing showed all extracts from isolated fungi with code IS-B1-A1, IS-B1-A2, IS-B1-T1, IS-B1-T2, IS-B1-B1, and IS-B1-B2 possessed antibacterial activity against Staphylococcus aureus with percentage inhibition of 51.1±2.6%; 84.6±3.1%; 72.7±7.9%; 82.9±7.6%; 65.6±0.8%; 88.2±2.8% at a concentration of 100 μg/mL.